What have we learned so far on the molecular pathogenesis of Werner syndrome using mutant mouse models of this human progeroid disorder?. (2018) - Lebel, Michel; Johnson, F. Brad
Abstract : Werner syndrome (WS) is a rare autosomal recessive disorder characterized by genomic instability and the premature onset of several age-associated phenotypes. The protein defective in WS patients (WRN) is a helicase/exonuclease involved in DNA replication, repair, telomere maintenance, and transcription. This review focuses on experimental mouse models that have been generated to understand the molecular impact of different mutations in the Wrn orthologue on oxidative stress, inflammation, telomere maintenance, and transcription in different tissues. Appropriate crosses between Wrn mutant mice and transgenic or knockout models of genes important in cell cycle or DNA repair genes have highlighted the importance of the WRN protein in biological processes regulating cell proliferation, senescence, and apoptosis. Finally, this short review recognizes the limitations and translational values of such mouse models.